Komitmen Organisasi Memoderasi Pengaruh Partisipasi Anggaran, Asimetri Informasi, dan Self Esteem pada Budgetary Slack - Pramesti, Putu Ayu; Sujana, I Ketut (E-Jurnal Akuntansi, 2020)
This study purposed to figure out the effect of budgeting participation, information asymmetry, and self esteem on budgetary slack with organizational commitment as moderated variable in the Regional Organization of Badung Regency. The population in this study consisted by Head of Regional Organization, Head of Planning and Reporting and Head of Financial from the Regional Organization Unit of Badung Regency. Total number of respondents were 102 respondents by using saturated sampling method. Data analysis technique processed using Moderation Regression Analysis (MRA). The results showed that budgeting participation has a positive effect on budgetary slack, while information asymmetry and self esteem have a negative effect on budgetary slack. Organizational commitment proved to weaken the relationship between of budgeting participation, information asymmetry and self esteem on budgetary slack. Keywords: Budgetary Slack; Budgeting Participation; Information Asymmetry; Self Esteem; Organizational Commitment.